CS-TE Abstraction Framework: Ballet Teaching, Training, and Testing Station with Kinect Sensors and EEG Measurement - Apirath Limmanee; Sathit Pairoch; Montri Phothisonothai (My University, 2024)
This article advocates the use of abstraction in the design of a standardized ballet learning, training, and testing station. The framework could also be applied to other types of dancing as well. On the one hand, the state-of-the-art engineering research approach focuses on mathematical models, algorithm, complexity, and efficiency of gesture recognition processes. On the other hand, our approach is top-down, where lower-level abstraction inherits the concepts from the upper-level. And the very top-level concepts are in accordance with how dancing artists really think while they generate their work of arts.
Keywords: Human Motion and Animation; Human Pose and Action Recognition; Video Analysis and Summarization